From HRM Practices to Organizational Citizenship Behavior: Unraveling the Mediating Role of Job Satisfaction - Dahlan Gunawan; Afit Afrizal (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study addresses the limited empirical evidence on how human resource management (HRM) practices promote organizational citizenship behavior (OCB) through job satisfaction within the petrochemical industry, a strategic sector where voluntary employee behavior is essential for operational safety and organizational sustainability. Grounded in Social Exchange Theory, the study aims to examine the direct effect of HRM practices on OCB and the mediating role of job satisfaction among employees of petrochemical companies in Cilegon, Indonesia. A quantitative explanatory survey was conducted involving 223 employees selected through proportional stratified random sampling from seven petrochemical companies. Data were collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that HRM practices significantly enhance job satisfaction and OCB, while job satisfaction also exerts a significant positive effect on OCB. Furthermore, job satisfaction partially mediates the relationship between HRM practices and OCB, indicating that positive HRM practices encourage discretionary employee behaviors both directly and indirectly through improved workplace satisfaction. These findings extend Social Exchange Theory by demonstrating the psychological mechanism through which HRM practices foster positive employee behavior in a high-risk industrial setting. Practically, the study highlights the importance of strengthening compensation, rewards, and employee-centered HRM policies to cultivate higher organizational citizenship behavior.